Brown Amphibole as Tracer of Tectono-Magmatic Evolution of the Atlantis Bank Oceanic Core Complex (IODP Hole U1473A). (1st September 2022) - Ferrando, Carlotta; Tribuzio, Riccardo; Lissenberg, C Johan; France, Lydéric; MacLeod, Christopher J; Basch, Valentin; Villeneuve, Johan; Deloule, Etienne; Sanfilippo, Alessio
Abstract: Brown amphibole is a minor but common mineral component in lower oceanic crust. It is generally interpreted as products of migrating SiO2 and H2 O-rich fluids or melts, which can be either residual melts from advanced magmatic differentiation of Mid-Ocean Ridge Basalt (MORB), or hydrothermal fluids including a seawater component. Within the lower oceanic crust exhumed at the Atlantis Bank Oceanic Core Complex, along the ultraslow Southwest Indian Ridge, brown amphibole is ubiquitous in all lithologies from olivine- to oxide-gabbros and diorites, including both undeformed and plastically deformed varieties. We here show the results of a systematic petrological study conceived to unravel the nature of the H2 O-rich component recorded in brown amphiboles and document: (i) the evolution of migrating melts during the magmatic stage and (ii) different extents of melt-bearing deformation events recorded throughout the entire crustal transect. The low Cl contents and the light over heavy rare earth elements (LREE/HREE) ratios and high Ti contents in brown amphiboles indicate they crystallized from melts with a magmatic hydrous component. Consistently, their δ 18 O values are in equilibrium with Mid-Ocean Ridge Basalt (MORB) composition, except for diorite amphiboles that possibly record the local assimilation of altered minerals. In undeformed olivine gabbros, interstitial pargasite crystallized at hypersolidus conditions ( 1000°C) from the melt residual after late stages of MORB differentiation. We speculate that before the olivine gabbro crystal mush reached fully solid state, some aliquots of residual melts were extracted and accumulated within discrete intervals. There, ferrobasaltic melts differentiated through the early crystallization of Fe-Ti oxides and clinopyroxene as liquidus phases, ultimately forming the oxide gabbros. This process promoted rapid Si enrichment and depletion in Fe, Ti, V in the residual melt, later extracted to form the crosscutting diorite veins. The mylonitic olivine gabbros record high-temperature plastic deformation ( 900°C ± 50°C) under hypersolidus conditions, involving melts residual from previous crystallization of the gabbroic rock. Further solid-state plastic deformation led to substantial grain size reduction and, consequently, to an increase in porosity. This created pathways for subsequent melt focusing, which likely represent late-stage differentiated melts migrating throughout the lower crustal section. This study shows that brown amphibole in the Atlantis Bank lower oceanic crust is the crystallization product of melts residual from advanced magmatic differentiation, which are also locally involved in the plastic deformation events during crustal accretion.